Cross-Sectional Associations of Body Adiposity, Sedentary Behavior, and Physical Activity with Hemoglobin and White Blood Cell Count - Koivula Tiia; Lempiäinen Salla; Laine Saara; Sjöros Tanja; Vähä-Ypyä Henri; Garthwaite Taru; Löyttyniemi Eliisa; Sievänen Harri; Vasankari Tommi; Knuuti Juhani; Heinonen Ilkka H A (MDPI, 2022)
Background: This study examined whether hemoglobin (Hb) and white blood cell count (WBC) associate with body adiposity and other cardiometabolic risk factors, as well as accelerometer-measured sedentary behavior (SB) and physical activity (PA), when adjusted for body mass index (BMI).
Methods: The cross-sectional analysis included 144 participants (42 men) with a mean age of 57.0 years and a mean BMI of 31.7 kg/m2. SB and standing time, breaks in sedentary time and PA were measured during four consecutive weeks with hip-worn accelerometers. A fasting blood sample was collected from each participant during the 4-week measurement period and analyzed using Sysmex XN and Cobas 8000 c702 analyzers. Associations of WBC, Hb and other red blood cell markers with cardiometabolic risk factors and physical activity were examined by Pearson's partial correlation coefficient test and with linear mixed regression models.
Results: In sex- and age-adjusted correlation analyses both BMI and waist circumference correlated positively with Hb, WBC, red blood cell count (RBC), and hematocrit. Hb was also positively correlated with systolic blood pressure, insulin resistance scores, liver enzymes, LDL, and triglyceride levels. Sedentary time correlated positively with WBC, whereas standing time correlated negatively with WBC. Lying time correlated positively with WBC, RBC, hematocrit, and Hb. Regarding SB and PA measures, only the association between lying time and RBC remained significant after adjustment for the BMI.
Conclusion: We conclude that body adiposity, rather than components of SB or PA, associates with Hb levels and WBC, which cluster with general metabolic derangement.